Perception of School Climate and Masculinity on Bullying Behavior - Hendra Kurniawan; Kamsih Astuti (Psycho Holistic, 2021)
Bullying has an impact on the educational process that does not run conducive; the conditions of the learning atmosphere and the learning process are often obstacles so that the potential development of students does not develop optimally, both physically, intellectually, emotionally and spiritually. Bullying is defined as negative behaviour shown by a person or group, done repeatedly and occurs from time to time. This study aims to find out the role of school climate perceptions and masculinity on bullying. The subjects used were 136 students of SMP X who had been bullies. The results of the multiple regression test were R = 0.792, and the F value was 112.149 (p <0.01). The effective contribution of perceived school climate and masculinity to predict bullying was 62.2% and the remaining 37.8%—other factors not examined in this study. The school climate variable has a standardized beta coefficient of -0.380 with a value of -7605 and a significance level of 0.000 (p <0.01), which means that the school climate has a major influence on bullying. The other independent variable is masculinity, with a beta coefficient of 0.436 with a t-value of 7.327 and also a significant level of 0.000 (p<0.01), meaning that masculinity has an influence on bullying. According to these results, it can be concluded that the school climate perception variable and masculinity together play a role in bullying